Answer: x=6 y=6
Step-by-step explanation:
![\displaystyle\\\left \{ {{4x-3y=6} \atop {6x-5y=6}} \right.\\](https://tex.z-dn.net/?f=%5Cdisplaystyle%5C%5C%5Cleft%20%5C%7B%20%7B%7B4x-3y%3D6%7D%20%5Catop%20%7B6x-5y%3D6%7D%7D%20%5Cright.%5C%5C)
Since the right parts of the equation are equal, therefore the left parts of the equation are also equal:
![4x-3y=6x-5y\\4x-3y+5y=6x-5y+5y\\4x+2y=6x\\4x+2y-4x=6x-4x\\2y=2x\\](https://tex.z-dn.net/?f=4x-3y%3D6x-5y%5C%5C4x-3y%2B5y%3D6x-5y%2B5y%5C%5C4x%2B2y%3D6x%5C%5C4x%2B2y-4x%3D6x-4x%5C%5C2y%3D2x%5C%5C)
Divide both parts of the equation by 2:
![y=x\\Hence,\\4x-3x=6\\x=6\\Thus,\\x=y=6](https://tex.z-dn.net/?f=y%3Dx%5C%5CHence%2C%5C%5C4x-3x%3D6%5C%5Cx%3D6%5C%5CThus%2C%5C%5Cx%3Dy%3D6)
Let the number of $1 bill be x and $5 bill be y
x=5y
5y+y=48
6y=48
x=40
y=8
number of $1 bill= 40
number of $5 bill = 8
Average acceleration = (173-0)/39=4.44m/s^2
<span>x−27=67 solve for x
Add 27 to both sides, then
x -27 +27 = 67 + 27
x = 94
</span>